2020
DOI: 10.1371/journal.pbio.3000783
|View full text |Cite
|
Sign up to set email alerts
|

Two unequally redundant "helper" immune receptor families mediate Arabidopsis thaliana intracellular "sensor" immune receptor functions

Abstract: Plant nucleotide-binding (NB) leucine-rich repeat (LRR) receptor (NLR) proteins function as intracellular immune receptors that perceive the presence of pathogen-derived virulence proteins (effectors) to induce immune responses. The 2 major types of plant NLRs that "sense" pathogen effectors differ in their N-terminal domains: these are Toll/interleukin-1 receptor resistance (TIR) domain-containing NLRs (TNLs) and coiled-coil (CC) domain-containing NLRs (CNLs). In many angiosperms, the RESISTANCE TO POWDERY MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
201
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(210 citation statements)
references
References 66 publications
6
201
3
Order By: Relevance
“…NLRs are classified as coiled-coil (CC), TOLL-INTERLEUKIN 1 RECEPTOR (TIR) or RPW8-like CC (CCR; HELO-domain) NLRs based on the different structures of their N-terminal domains 9 . Two subfamilies of CCR-type NLRs, with ADR1 and NRG1 as founding members, function downstream of many sensor CC-NLRs and most, if not all, TIR-NLRs and are thus considered as helper NLRs (hNLRs) 1012 . In Arabidopsis , the two hNLR groups function together with the EDS1-family of lipase-like proteins to relay signals downstream of sensor NLRs in ETI 10,1315 .…”
Section: Introductionmentioning
confidence: 99%
“…NLRs are classified as coiled-coil (CC), TOLL-INTERLEUKIN 1 RECEPTOR (TIR) or RPW8-like CC (CCR; HELO-domain) NLRs based on the different structures of their N-terminal domains 9 . Two subfamilies of CCR-type NLRs, with ADR1 and NRG1 as founding members, function downstream of many sensor CC-NLRs and most, if not all, TIR-NLRs and are thus considered as helper NLRs (hNLRs) 1012 . In Arabidopsis , the two hNLR groups function together with the EDS1-family of lipase-like proteins to relay signals downstream of sensor NLRs in ETI 10,1315 .…”
Section: Introductionmentioning
confidence: 99%
“…The similar phenotypes of adr1 triple with pad4 (Phytoalexin deficient 4) mutants (Dong et al, 2016), and the additive effects between SAG101 and PAD4 (Rietz et al, 2011) or NRG1s and ADR1s (Lapin et al, 2019; Saile et al, 2020; Wu et al, 2019) allude to an EDS1-ADR1-PAD4 signaling module that works in parallel with an EDS1-NRG1-SAG101 module to regulate downstream events in TNL immunity. To test this further, higher order mutants combining loss-of-function mutations from different modules were generated in snc1 background.…”
Section: Resultsmentioning
confidence: 99%
“…CC R domains from both NRG1 and ADR1 families can induce defense responses, including cell death (Collier et al, 2011). The NRG1 family functions broadly downstream of TNLs (Peart et al, 2005; Qi et al, 2018), while the ADR1 family is involved in ETI responses mediated by TNLs and a few CNLs (Bonardi et al, 2011; Dong et al, 2016; Saile et al, 2020). There is a co‐occurrence signature among TNLs, SAG101, and NRG1, as these proteins are absent from monocots and several dicot species ( Aquilegia coerulea , Erythranthe guttata ) (Collier et al, 2011; Wagner et al, 2013).…”
Section: Diversity and Classification Of The Cnl CC Domainmentioning
confidence: 99%
“…Furthermore, the EDS1‐SAG101‐NRG1 module mediates cell death signaling downstream of TNL/TIR in Arabidopsis and N. benthamiana (Gantner et al, 2019; Lapin et al, 2019). By contrast, PAD4 and ADR1 are widely present in angiosperm species (Collier et al, 2011; Wagner et al, 2013), and the EDS1‐PAD4 heterodimer is likely to function together with ADR1 in plant immunity (Gantner et al, 2019; Lapin et al, 2019; Saile et al, 2020). Genetic analyses have demonstrated that NRG1 and ADR1 contribute specific, redundant, or synergistic roles in basal resistance, ETI and regulation of defense gene expression (Wu et al, 2019; Saile et al, 2020).…”
Section: Diversity and Classification Of The Cnl CC Domainmentioning
confidence: 99%